An Analysis on Students’ Difficulties in Speaking - Baiq Suprapti handini; Ari Prasetyaningrum; Selamet Riadi Jaelani; Muhammad Faza Fauzan Azima (LPPM Universitas Bumigora Mataram, 2021)
The purpose of this research was to analyze the students’ difficulties in speaking English especially in introducing them self at MTS NW Al Hidayah Baremayung. Besides, the researcher also wanted know what the students’ difficulties in speaking English and what the factors of students difficulties in speaking English especially in introducing them self. The method of collecting data are observation, recording, and interview. The data were taken from the subject of the research in the form of teaching learning process, interview and recording. The research finding show that the students difficulties in speaking English especially in introducing them self are: (a) the student’s low vocabulary mastery. (b) the students had difficulties in pronouncing certain words because, English words are different between pronunciation and writing. (c) the students were still confused in arranging words. Then, there were still some mistakes in their grammar. (d) the students were often afraid of speaking English because they were worried of making mistakes. They were not confident and nervous when they introducing themselves.